Effect graphite on magnesium diboride superconductivity synthesized by combustion method under argon pressure: Part II - S. Tolendiuly (Croatian Metallurgical Society, 2022)
There are many various techniques to synthesize the superconductors based on magnesium diboride. In this paper, we attempted to obtain a superconducting magnesium diboride in a way by using a High-Temperature Centrifuge and investigated how a centrifugal force can be effect on superconducting parameters of MgB2 during solid-state combustion. It was the first superconductor based on magnesium diboride synthesized under the influence of centrifugal force in the high temperature centrifuge during solid phase process. As a result of this research, we could determine that a centrifugal force do not impact considerably on the critical transition temperature of the MgB2 samples (stay at around 37,5 – 38 K). However, it was found that the value of a centrifugal force could effects on the critical current density (Jc) of the samples.